2021
DOI: 10.3390/clinpract11030065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Thyroid Abnormalities and Its Association with Anemia in ASIR Region of Saudi Arabia: A Cross-Sectional Study

Abstract: The thyroid gland plays a significant role in the metabolism and proliferation of blood cells; hematological disorders are frequently observed in patients with thyroid disorders, and the most frequent problem is anemia. The main objective of this research work is to evaluate the prevalence and types of thyroid dysfunction and their association with anemia in different gender stratified by age in the Asir region of Saudi Arabia. Four years of data from July 2016 to July 2020 for 9992 study subjects were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 33 publications
5
34
2
Order By: Relevance
“…In the United States, the American Thyroid Association estimated that at least 20 million US adults have some form of thyroid disease; interestingly, the majority of the thyroids were unaware of their disease status ( 7 ). In Saudi Arabia, the overall prevalence was 49.76%, among which subclinical hypothyroidism was the most prevalent type (3922/9992), followed by primary hypothyroidism (530/9992) ( 8 ). However, studies found that the prevalence of thyroid dysfunction varies by age, gender, race/ethnicity, geographical distribution, and the amount of dietary iodine intake ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the American Thyroid Association estimated that at least 20 million US adults have some form of thyroid disease; interestingly, the majority of the thyroids were unaware of their disease status ( 7 ). In Saudi Arabia, the overall prevalence was 49.76%, among which subclinical hypothyroidism was the most prevalent type (3922/9992), followed by primary hypothyroidism (530/9992) ( 8 ). However, studies found that the prevalence of thyroid dysfunction varies by age, gender, race/ethnicity, geographical distribution, and the amount of dietary iodine intake ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 14 ] HbA1c level is commonly used as a clinical indicator for glycemic control and is used as a tool to diagnose people with unidentified diabetes or who are at risk. [ 17 ] The relationship between UA levels and impaired glucose metabolism has long been a hot research topic. A large number of studies have demonstrated the “bell” fit association between UA and plasma glucose level.…”
Section: Discussionmentioning
confidence: 99%
“…T-test was used to assess the difference between group means of parametric variables, while Mann–Whitney and Kruskal–Wallis tests were used to compare groups of independent nonparametric variables. [ 16 17 ] Logistic regression analysis and receiver operator characteristics (ROCs) curves were used to analyze biochemical parameters against the risk of diabetes in the study population. [ 30 31 ] The significance level was set at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations